Nutritional Quality Differences of Pleurotus sajor-caju M2145 and Pleurotus ostreatus M2191 in Mixed Substrates of Brewer’s Spent Grain Supplemented with Lignocellulosic Residues - Demissew Gebeyehu; Asmamaw Tesfaw (International Journal of Agronomy)
Oyster mushrooms are a type of lignocellulolytic fungus that is used for both culinary and medicinal purposes. The purpose of this study was to assess the nutritional value, biological efficiency, and yields of P. ostreatus M2191 and P. sajor-caju M2145 grown on spent grain from breweries that have been supplemented with various agricultural wastes. The primary substrates at varying compositions included sawdust, wheat straw, cottonseed, teff straw, bean straw, and brewer’s spent grain. Two percent gypsum and eight percent wheat bran were added as supplements to the primary substrates. A daily assessment of the growth and development of the Pleurotus species was conducted during their aseptic cultivation. A combination of 25% brewer’s spent grain and 75% cottonseed produced the highest biological efficiency and nutritional attributes. The lowest nutritional compositions, yields, and biological efficiency were found when eucalyptus sawdust was used alone or in combination with other agroindustrial residues. Under the weather conditions of Debre Berhan, P. ostreatus M2191 and P. sajor-caju M2145 could be grown using agricultural residues and leftover grains from the brewery.